"I became a beggar": life experience reports of former homeless people sheltered in a brazilian confessional institution - Milene Pescatori Packer; Rosângela Higa; Cassia Regina Rodrigues Varga; Claudinei José Gomes Campos; Egberto Ribeiro Turato (Universidade Federal de Santa Maria, 2015)
Aim: to analyze the life experiences of former homeless alcohol users sheltered in a Confessional Institution. Method: the study is based on the clinicalqualitative method. From August 2007 to May 2008, semi-structured interviews were carried out with residents of a philanthropic organization in the state of São Paulo. The saturation criterion defined a sample of eight participants. Results: three categories were composed through the content analysis technique: You get embarrassed: expresses tendency to isolation or forming groups; I became a beggar: shows the breakdown of social life and loss of identity; The past will not return: demonstrates an attempt to get rid of their self-image, social denial and identification with the new roles. Conclusion: to survive, the former homeless person denies central elements of their identity and experiences the reconstruction of a new identity. In order to return to the former home/society, it is necessary to recompose the lost identity